Discovery of Elytrurini in Wallacea with a description of Exophthalmida elytrodon sp. nov. from Morotai Island (Coleoptera: Curculionidae: Entiminae) - Yunakov, Nikolai; Bollino, Maurizio; Pancini, Lorenzo; Anderson, Robert (Zootaxa, 2024)
This study presents the first record of the weevil tribe Elytrurini in Wallacea with the discovery and description of a new species, Exophthalmida elytrodon Yunakov, Bollino, Pancini and Anderson sp. nov., from Morotai Island. Exophthalmida elytrodon sp. nov. is distinguished by its unique morphological traits, including long preapical spines on the elytral declivity in females, which sets it apart from other species in the genus. Remarkably, similar spines are characteristic of other Entiminae of the Australasian region, i.e. Elytrurus Boisduval, 1835 and particularly Ottistira Pascoe, 1872. Distribution maps of Exophthalmida Faust, 1892 and Elytrurni are given. This discovery challenges previous biogeographic assumptions about the distribution of Elytrurini, which were thought to be confined to regions eastward of New Guinea.